Insights From a New 1-ha Permanent Forest Plot Reveal Differences Between Habitat Type and Similarities Between Forest Type in the Southwestern Amazon - Fortier, R.P.; Corahua-Espinoza, T.; Swamy, V.; Feeley, K.J.; Gallice, G. (John Wiley and Sons, 2025)
The southwestern Amazon is a biodiversity hotspot home to some of the oldest permanent forest dynamics plots in the basin. Despite the region's abundance of plots, we still know relatively little about how tree diversity and composition change across the region's precipitation gradient, between habitat types, and how disturbed and managed forests compare to protected, old-growth forests since the majority of forest plots are located in protected forests. In this study, we first described a new 1-ha permanent forest dynamics plot at the confluence of agricultural land and managed Brazil nut forest. We then compared the plot to others in the region to evaluate the relationship between precipitation and plot diversity, compositional differences between floodplain and terra firme forest, and differences in forest dynamics between our disturbed forest plot and old-growth forest plots. Contrary to large-scale patterns in tree diversity, we found no relationship between precipitation and tree alpha diversity for plots in the southwestern Amazon. There were, however, clear compositional differences between floodplain and terra firme forests. Annual change in the aboveground biomass of the new plot was higher than in other plots in the region. Similarly, annual rates of mortality and recruitment were lower and higher, respectively, in the new plot compared to the other plots. The floristic and structural similarities between plots in disturbed or managed forests and plots in old-growth forests indicate a high resilience of tropical forests to low-intensity disturbances. Our findings thus provide evidence that low-intensity logging and low-impact Brazil nut harvesting in the southwest Amazon do not significantly alter forest structure and composition in the medium to long term. Our new plot bolsters the representation of disturbed and managed forests in plot databases and will be an important resource for future studies of large-scale patterns of forest diversity, structure, and dynamics.
Keywords: Floodplain; Forest dynamics; Old-growth forest; Geography; Forest plot; Ecology; Biodiversity; Amazon rainforest; Secondary forest; Habitat; Forest management; Forestry; Agroforestry; Environmental science; Biology; https://purl.org/pe-repo/ocde/ford#1.06.13